Laser welding process in PP moulding parts: evaluation of seam performance - Oliveira, N. (2015)
The Polypropylene is one of the most versatile polymer materials used in the industry. Due to this versatility, it is possible to use it in different products. This material can also be mixed with several additives namely glass fiber, carbon nanotubes, etc. This compatibility with different additives allows also obtaining products with characteristics that goes from an impact absorber to an electricity conductor. When is necessary to join components in PP they could be welded through hot plate, ultrasonic weld and also by laser. This study had the objective of study the influence of several variables, capable of influence the final quality of the seam. In this case were studied variables of the injection molding process as mold temperature and cooling time. Was also studied laser welding variables and different materials. The results showed that the variables that have the most influence were mould temperature, laser velocity and laser diameter. The seams were analyzed using Optical Microscopy technique. The seams showed perfect contact between the materials analyzed, despite the high standard variation presented in the mechanical testes.